A Case Report of Myeloid Sarcoma in a Child - TT Valiev; AM Kovrigina; TR Panferova; TL Ushakova; IN Serebryakova; NN Tupitsyn; LYu Grivtsova; II Matveeva; EV Mikhailova; AV Popa; GL Menkevich (Клиническая онкогематология)
The diagnosis of myeloid tumors is based on a complex approach and causes significant difficulties especially in young children. Morphologic, immunologic, cytogenetic, molecular and biologic data on myeloid sarcoma are presented based on the literature data and own clinical case. Treatment results of myeloid sarcoma (especially in the high risk group) are unsatisfactory and should be improved.